Developing Arabic Learning with Management System (Moodlecloud) at MTs. NU Miftahul Ulum Margasari - Akhmad Aufa Syukron; R Umi Baroroh (Arabic Education Program IAIN Pekalongan, 2019)
This research aims to: (1) find out the actual conditions of learning Arabic at MTs NU Miftahul Ulum Margasari; (2) explained the development of Learning Management System (Moodlecloud) Arabic language learning on Arabic subjects at MTs NU Miftahul Ulum Margasasri; (3) to find out the form of implementation of LMS (Moodlecloud) -based Arabic language learning at MTs NU Miftahul Ulum Margasari. This research uses the Research and Development (R & D) method. This research used observation and questionnaire on scale of 1-5. The results of this study indicate that: (1) the conditions at MTs NU Miftahul Ulum Margasari support to LMS-based Arabic language learning (Moodlecloud) application; (2) This LMS (Moodlecloud) Arabic language learning was developed according to the needs of LMS users, especially in terms of display and learning materials in Arabic; (3) LMS (Moodlecloud) Arabic language learning at MTs NU Miftahul Ulum Margasari is very acceptable, and can be applied to other subjects.